The Urgency of Green Banking Regulations in Indonesia in the Implementation of Sustainable Development - Kartiko, Nafis Dwi; Indradewi, Astrid Athina; Sugianto, Fajar (Fakultas Hukum Universitas Lampung, 2024)
This research highlights significant gaps in Indonesia's green banking regulations, particularly the lack of stringent sanctions and clear enforcement frameworks for sustainable finance principles. While the Financial Services Authority Regulation No. 51/POJK.03/2017 addresses environmental sustainability, it fails to impose effective penalties on banks that contribute to environmental degradation. As a result, green banking in Indonesia remains largely a voluntary initiative due to insufficient regulatory measures. This research employs a normative legal research design, utilizing both conceptual and statutory approaches. It advocates for the implementation of stricter penalties and enhanced oversight to ensure compliance with sustainability standards among financial institutions, thereby facilitating the transition to a green economy. Furthermore, the Sustainable Development Goals (SDGs) underscore the importance of indicators related to economic, social, and environmental sustainability, which green banking can help achieve. The proposed revised regulatory framework should include stringent sanctions for violations by both banks and customers, ensuring that financial institutions actively contribute to environmental protection.